Towards Matched Pairs of Porphyrin–ReI/99mTcI Conjugates that Combine Photodynamic Activity with Fluorescence and Radio Imaging. Issue 6 (23rd February 2014) - Gianferrara, Teresa; Spagnul, Cinzia; Alberto, Roger; Gasser, Gilles; Ferrari, Stefano; Pierroz, Vanessa; Bergamo, Alberta; Alessio, Enzo
Abstract We recently prepared two novel water soluble porphyrins bearing a single peripheral chelator, either diethylenetriamine (1) or bipyridyl (2), tethered to one meso position. The preparation of their conjugates with a fac‐{99mTc(CO)3}+ fragment and the potential of these resulting conjugates as fluorescence and radio imaging tools were also described. In this work, we focused on the corresponding non‐radioactive analogues that bear the fac‐{Re(CO)3}+ fragment (diethylenetriamine 3 and bipyridyl 4). We report on the uptake, in vitro PDT activity, and cellular localization of ReI conjugates 3 and 4 in comparison to the parent porphyrins 1 and 2. Compounds 1–4 have modest or negligible cytotoxicity in the dark against HeLa human cervical cancer cells but become remarkably cytotoxic after exposure to moderate doses of red visible light (590–700 nm). This phototoxicity was found to be directly proportional to the total light dose. Although the four compounds show distinct uptake patterns, they have comparable PDT activity. Confocal fluorescence measurements showed that porphyrin 1 and its ReI conjugate 3 have different cellular localization patterns in HeLa cells.